2017
DOI: 10.31958/juris.v15i1.487
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CAPITAL ADEQUACY, LIQUIDITY, AND OPERATIONAL EFFICIENCY TO PROFITABILITY IN BANK SYARIAH MANDIRI (Period 2008 s.d. 2015)

Abstract: This research aimed at analyzing the effects of Capital Adequacy (CAR), liquidity (FDR) and operational efficiency (BOPO) toward profitability (ROA) in PT. Bank Syariah Mandiri (2008 to 2015. The effects of CAR, FDR and BOPO were measured quantitatively and correlated to the company's ROA by means of double linear regression formula. The object of the research was three-monthly financial report through 31 observations. The findings showed that CAR and BOPO had negative and significant effects toward ROA. FDR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Therefore, bank's management must be very careful in managing the bank so that operational costs were not too high. Banks must be able to maintain cost efficiency by reducing unnecessary costs (Ismaulina and Zulfadhli, 2016). These results supported the results of research by Adeyinka (2013) and Ariyani (2010) which discovered that OCOI had a significant and negative effect on profitability.…”
Section: Hypothesis Test Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, bank's management must be very careful in managing the bank so that operational costs were not too high. Banks must be able to maintain cost efficiency by reducing unnecessary costs (Ismaulina and Zulfadhli, 2016). These results supported the results of research by Adeyinka (2013) and Ariyani (2010) which discovered that OCOI had a significant and negative effect on profitability.…”
Section: Hypothesis Test Resultssupporting
confidence: 81%
“…These results supported the research of Sutrisno (2016), Akhtar et.al (2011 and Syafri (2012) which discovered that CAR had a significant but negative effect on bank's performance. Likewise, the findings of Ismaulina andZulfadhli (2016) andNorman et.al (2015) also discovered a significant and negative effect between CAR and profitability.…”
Section: Hypothesis Test Resultsmentioning
confidence: 82%
“…Therefore, bank management must be very careful in managing the bank so that operational costs are not too high. Banks must be able to maintain cost efficiency by reducing unnecessary costs (Ismaulina & Zulfadhli, 2016).…”
Section: Risk Management Factors Namely Operational Risk (Bopo) Affec...mentioning
confidence: 99%
“…Several studies have found that the capital adequacy ratio (CAR) has a significant but negative effect on bank performance. A study by Ismaulina and Zulfadhli (2017), for instance, found that CAR has a negative but significant effect on a bank's performance variable, the ROA. A similar finding was also revealed by Hersugondo, Anjani, and Pamungkas (2021) and Juwita, Raga, Prasetyo, and Rimawan (2018).…”
Section: Hypothesis Developmentmentioning
confidence: 99%